1969
DOI: 10.1104/pp.44.5.775
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Succinyl CoA Synthetase Activity in Etiolated Bean Leaves Caused by Illumination

Abstract: Abstract. The illumination of etiolated bean leaves (Phaseolus v2ulgaris) causes an increase in the activity of succinyl coenzyme A synthetase. Continuous white light or short periods of red or blue light followed by darkness will induce an increase with the highest activity at about 6 hr after the onset of illumination. Thereafter the activity decreases so that at 12 hr it is the same .as the initial dark activitv. Treatment with cycloheximide before illumination prevents the increase in activity. A number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Succinyl thiokinase, which forms succinyl-CoA, has been reported to be present in wheat chloroplasts (21), in Jerusalem artichoke mitochondria (23), and in etiolated bean leaf homogenates (31). If succinylCoA, produced in the mitochondrion is used there for ALA formation, then calculations based on respiration data from the lag phase of greening Chlamydomonas (22) and bean leaves (34) indicate that the succinyl-CoA that can be formed from a-ketoglutarate in the citric acid cycle is at least 100 to 1000 times that required for ALA formation.…”
Section: Resultsmentioning
confidence: 99%
“…Succinyl thiokinase, which forms succinyl-CoA, has been reported to be present in wheat chloroplasts (21), in Jerusalem artichoke mitochondria (23), and in etiolated bean leaf homogenates (31). If succinylCoA, produced in the mitochondrion is used there for ALA formation, then calculations based on respiration data from the lag phase of greening Chlamydomonas (22) and bean leaves (34) indicate that the succinyl-CoA that can be formed from a-ketoglutarate in the citric acid cycle is at least 100 to 1000 times that required for ALA formation.…”
Section: Resultsmentioning
confidence: 99%
“…Growth and illumination conditions are reported fully elsewhere (15). Seeds were germinated in darkness and used on the seventh day.…”
mentioning
confidence: 99%
“…The biosynthetic pathway of chlorophyll from A-aminolevuIinic acid has been located within the chloroplast (Carell and Kahn 1964), but information regarding the site of the enzymes involved in the production of succinyl CoA, one of the precursors of A-aminolevulinic acid is more contradictory. Steer and Gibbs (1969) noted a rapid formation of succinyl-CoA synthetase during the greening of etiolated bean leaves and Nandi and Waygood (1965) suggested that this en- Physiol. Plant.,25,197I| zyme was located within the chloroplast.…”
Section: Discussionmentioning
confidence: 99%